Plan and Analysis of closed loop Interleaved Buck converter for UPS Appliation - et. al, J. SREEDHAR (International Journal of Advanced Science and Technology, 2020)
Abstract— Choosing a right appropriate converter for an application is very important. There are many available DCDC converters, out of which some converters give appropriate desired results. Typical power supply requirements are size, cost, efficiency, temperature, accuracy, transient response. A simple method to step down the input source voltage is by using Buck converter. Though we can use linear regulators for the purpose of decreasing the input source voltage, linear regulators dissipates lot of power which is not suggested. This paper deals with the design and model of Buck converter for charging battery or for UPS application. Small signal analysis with open loop bode plot was also shown with its necessary analysis. Buck converter is a simple DC-DC converter suitable when low input power is available. In this paper, synchronous Buck converter is designed using Matlab/Simulink and the results were discussed.